2009
DOI: 10.1175/2008jamc1948.1
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Rain Integral Parameters during Tropical Convective, Transition, and Stratiform Rain at Gadanki and Its Application in Rain Retrieval

Abstract: In the present study the characteristics of rain integral parameters during tropical convective (C), transition (T), and stratiform (S) types of rain are studied with the help of Joss-Waldvogel disdrometer (JWD), L-band, and very-high-frequency wind profilers at Gadanki (13.58N, 79.208E). The classifications of three regimes are made with the help of an L-band wind profiler. For rain rate R , 10 mm h 21 larger drops are found in S type of rain relative to C and T rain, and for R $ 10 mm h 21 larger drops are f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 47 publications
5
53
0
Order By: Relevance
“…The DSDs characterized by size-controlled processes provide a limiting case for valid range of shape factor μ [Steiner et al, 2004]. From wind profiler measurements and MRR, the CCB processes are found to dominate among the raindrops during the tropical stratiform rain [Kirankumar et al, 2008;Sharma et al, 2009;Konwar et al, 2012a]. Although we do not have simultaneous X band radar observations of the storms under discussion, limited observations of the stratiform precipitating system for another day indicates presence of liquid hydrometeors below the melting layer ( Figure S1).…”
Section: Altitude and Temporal Variability Of Raindrop Size Distributmentioning
confidence: 94%
See 2 more Smart Citations
“…The DSDs characterized by size-controlled processes provide a limiting case for valid range of shape factor μ [Steiner et al, 2004]. From wind profiler measurements and MRR, the CCB processes are found to dominate among the raindrops during the tropical stratiform rain [Kirankumar et al, 2008;Sharma et al, 2009;Konwar et al, 2012a]. Although we do not have simultaneous X band radar observations of the storms under discussion, limited observations of the stratiform precipitating system for another day indicates presence of liquid hydrometeors below the melting layer ( Figure S1).…”
Section: Altitude and Temporal Variability Of Raindrop Size Distributmentioning
confidence: 94%
“…The scatter plots of Z-R relationships over Atlas et al, 1999;Ulbrich and Atlas, 2007;Rao et al, 2001;Sharma et al, 2009]. However, greater than unity value of the exponent suggest that rain processes are dominated by size-controlled processes.…”
Section: Z-r Relationships Over Mahabaleshwar and Comparison With Othmentioning
confidence: 95%
See 1 more Smart Citation
“…The A coefficients of the Z-R relations obtained for the nine rain events have a mean value of 288.63 with a standard deviation of 88.95 for stratiform rain. But for the convective rain, the A coefficients of the Z-R relations Several studies [25,26] have shown how the DSD, and therefore the Z-R relationship, varies geographically, with rainfall intensity. It is also stated in [25] that the coefficient A is smaller for stratiform rain and increases for increasing convective activity, while b behaves in the opposite manner (smaller for convective rain and larger for stratiform systems).…”
Section: Rain Classificationmentioning
confidence: 99%
“…But for the convective rain, the A coefficients of the Z-R relations Several studies [25,26] have shown how the DSD, and therefore the Z-R relationship, varies geographically, with rainfall intensity. It is also stated in [25] that the coefficient A is smaller for stratiform rain and increases for increasing convective activity, while b behaves in the opposite manner (smaller for convective rain and larger for stratiform systems). As expected, the coefficient A is larger for the tropical convective rain (Singapore) followed by the stratiform stage because of the presence of larger drops in these stages.…”
Section: Rain Classificationmentioning
confidence: 99%